The responses of vegetation water use efficiency to biomass density and CO2 balance in dryland of Central Asia during 21st century - Alphonse Kayiranga; Xi Chen; Xuexi Ma; Dative Ingabire; Tie Liu; Yaoming Li; Emeka Edwin Igboeli; Eldiiar Duulatov; Hubert Hirwa; Clement Nzabanita; Ping Hu (Ecological Indicators)
Water-use efficiency (WUE) is a critical component that links plant carbon (CO2) and water cycles through various aspects of plant ecosystem functioning. However, the variations of plant CO2 in response to water use efficiency (WUE) across temperate dryland ecosystems remains inadequately understood. In this study, we examined the patterns and magnitude of WUE effects on desert vegetation aboveground biomass (AGB) and carbon stocks (C. stocks) and related fluxes by utilizing multiple streams of state-of-the-art multispectral satellite imagery and polynomial model across the temperate drylands of Central Asia (CA) from 2000 to 2023. The results indicated an annual increase in desert vegetation AGB density of 0.04 ± 0.66 kg.m2. yr−1 and in C. stocks of 0.32 ± 0.85 kg C.m2. yr−1. The results showed also that during 2000–2023, the total biomass density and total C. stocks of the CA desert ecosystems were amounted to 5.52 ± 1.19 Gt and 3.12 ± 0.88 Pg C with 0.044 Pg C and 0.218 Pg C the actual total C. sources and C. sinks, respectively. Among the desert plants’ water fluxes, water use efficiency at canopy conductance (iWUE) showed a significant impact on C. stocks (R2 = 0.57) compared to desert ecosystem water use efficiency (vWUE) and water use efficiency at plant respiration (tWUE). These findings have implications on regional strategies for CO2 controls and climate change mitigations and adaptation along the different global desert ecosystems.